Heterometallic rare-earth metal complexes with imino-functionalized 8-hydroxyquinolyl ligands: synthesis, characterization and catalytic activity towards hydrophosphinylation of trans-β-nitroalkene. (14th May 2015) - Yuan, Qingbing; Zhou, Shuangliu; Zhu, Xiancui; Wei, Yun; Wang, Shaowu; Mu, Xiaolong; Yao, Fangshi; Zhang, Guangchao; Chen, Zheng
Abstract : The heterobimetallic complexes exhibited high catalytic activities on the hydrophosphinylation of β-nitroalkenes. Abstract : Reactions of rare-earth metal amides [(Me3 Si)2 N]3 RE(μ-Cl)Li(THF)3 with different equiv. of 2-(2, 6-diisopropylphenylimino)-8-hydroxyquinoline (1 ) afforded different heterometallic rare-earth metal complexes, and catalytic activity of the resulting complexes was investigated. Reactions of rare-earth metal amides [(Me3 Si)2 N]3 RE(μ-Cl)Li(THF)3 (RE = Y, Er, Dy) with 1 equiv. of compound1 afforded the heterobimetallic rare-earth metal and lithium complexes2–4 bridged by the oxygen atom of 2-(2, 6-diisopropylphenylimino)-8-hydroxyquinoline and the nitrogen atom of N(SiMe3 )2 . However, the treatment of rare-earth metal amides [(Me3 Si)2 N]3 RE(μ-Cl)Li(THF)3 (RE = Sm, Er, Yb) with 2 equiv. of compound1 gave different heterobimetallic rare-earth metal and lithium complexes5–7 bridged by the oxygen atoms of 2-(2, 6-diisopropylphenylimino)-8-hydroxyquinoline. Complex6 can also be prepared by the treatment of3 with 1 equiv. of1 . Complexes2–7 were fully characterized using spectroscopic methods, elemental analyses and single crystal X-ray diffraction. Investigation of the catalytic properties of the complexes indicated that all complexes exhibited a high catalytic activity towards the addition of diphenylphosphine oxide to trans -β-nitroalkenes to afford β-nitrophosphonates under mild conditions.